DER-DIE-DAS Article Play Method in Improving German Vocabulary Mastery - Sahat Taruli Siahaan; Lusiana Simamora; Nancy Angelina Purba (EQUATOR SINAR AKADEMIA, 2022)
This Community Service activity (PkM) aims to socialize the Der-Die-Das artikel playing method in increasing mastery of foreign language vocabulary, especially German. The location of this service is at SD Negeri 091254 Batu Onom Pematang Siantar. The time of this community service activity is carried out on Wednesday, August 3, 2022 at 10.00-12.00 WIB. The target of this service is its teachers in order to be able to apply a variety of methods in elementary school classes in face-to-face learning. The results of this PkM activity show that the service has succeeded in educating elementary school teachers at SD Negeri 091254 Batu Onom Pematang Siantar on the Der-Die-Das method, which has added a reference to language learning methods at the elementary school level. Simulations have also been carried out on elementary school teachers in order to facilitate teachers' understanding of the implementation steps. The elementary school teachers seemed enthusiastic in participating in community service workshop/training and simulations organized by the PkM team of FKIP lecturers at HKBP Nommensen Pematang Siantar University. This was marked by the presence of teachers on the day of the PkM workshop/training and socialization and the teachers’ wish to always follow the upcoming PkM activities.